Development of Health Monitoring System for Coma Patients - Mohd Yusoff, Ahmad Adam Solihin; Adon, Mohamad Nazib (Evolution in Electrical and Electronic Engineering, 2022)
HHealth screening and body condition are very important in determining a person’s physical status or health issues, as well as early prevention, especially for a patient in a comatose state. Some of the coma patient’s condition is critical and require strict supervision. However, hospitals and health centers still use traditional technology or employ cable media to communicate patient data information. Hence, this project is developed aimed to solve all of these issues. It deployed the usage of three sensors which is pulse oximeter sensor, temperature sensor, and flex sensor with command processing within Arduino IDE software for health parameter measurement and embedded with the Internet of Things (IoT) application which is the Blynk application. This project is designed to display the heart rate, oxygen level, body temperature, and movement of coma patients on the Blynk application for cloud users. The health parameter is measured 5 times for 1 minute from a healthy subject aged 24 years old. The result shows that different body fitness can affect the heart rate value. Subjects with the fitted body show a low reading value between 60 to 61 beats per minute. Subjects with a below-average body show the reading value of heart rate between 72 to 78 beats per minute. And the last subject with an unfit body shows a value heart reading between 92 to 99 beats per minute. All three subjects show a normal oxygen level reading. From these three readings, a conclusion that can be made is the reading value of heart rate can be affected by the fitness of the body, and the pulse oximeter function normally with a small percentage of error in reading value. In conclusion, it is predicted that this project is capable to measure the important parameter in remote monitoring systems and advance healthcare technology in Malaysia.